أثر تطبيق المسؤولية الاجتماعية على أداء الموارد البشرية دراسة ميدانية الدى مديرية الكهرباء والغاز بالوادي - سفيان خليل; رانيا عويوش; بشير محلو (university of eloued جامعة الوادي, 2024)
"هدف هذه الدراسة إلى معرفة أثر المسؤولية الاجتماعية من طرف مؤسسة جاد مواردها البشرية على أدائهم، اعتبارا أن الموارد البشرية من أهم الأطراف التي يجب على المنظمة أن تؤدي مسؤولياتها الاجتماعية الجاهها، حيث يعتبر الالتزام المسؤول اتجاه المورد البشري ضرورة ملحة للرفع من أداءه أجريب الدراسة بالاعتماد على أسلوبين متكاملين الأول وثائقي (وصفي) بالاطلاع على عدد من الأدبيات لتوضيح الخلفية النظرية للمسؤولية الاجتماعية وأداء الموارد البشرية، أما الأسلوب الثاني مسحي (خليلي) عن طريق دراسة استكشافية من خلال الاستبيان كأداة لجمع البيانات، إذ تم قياس معامل الصدق حيث أنه تم التوصل إلى درجة عالية من الشباب لعينة مكونة من (60) فردا تم تحليل البيانات باستخدام الحزمة الإحصائية (SPSS) وأدوات إحصائية وصفية وخلصت الدراسة إلى جملة من النتائج كشفت نتائج الدراسة عن وجود أثر للمسؤولية الاجتماعية وكل من أبعاده الأربعة التوظيف تدريب والتطوير، نظام الأجور والحوافر الخدمات الاجتماعية في حين أنها محل لم يؤثر بعد تقييم الأداء)، على أداء الموارد البشرية لدى المؤسسات محل الدراسية " "This study aims to know the impact of social responsibility on the part of an organization towards its human resources on their performance, given that human resources are one of the most important parties towards which the organization must fulfill its social responsibilities, as responsible commitment towards the human resource is considered an urgent necessity to increase its performance. The study was conducted based on two complementary methods: the first was documentary (descriptive) by reviewing a number of literature to clarify the theoretical background of social responsibility and human resource performance. The second method was survey (analytical) through an exploratory study through the questionnaire as a tool for collecting data. The validity coefficient was measured as it A high degree of reliability was achieved for a sample of (60) individuals. The data was analyzed using the statistical package (SPSS) and descriptive statistical tools. The study concluded with a number of results. The results of the study revealed the existence of an impact of social responsibility and each of its four dimensions: (recruitment, training and development, wages and incentives system, social services), while it has been recorded that it has not yet affected (performance evaluation) on the performance of human resources at... Institutions under study. "
Keywords: المسؤولية الاجتماعية، إدارة الموارد البشرية، أداء الموارد البشرية social responsibility; human resources management; human resources performance.